Synthesis of spiroindanes by palladium-catalyzed oxidative annulations of non- or weakly activated 1,3-dienes involving C–H functionalization - Khan, Imtiaz; Chidipudi, Suresh Reddy; Lam, Hon Wai (Royal Society of Chemistry, 2015)
The synthesis of spiroindanes by the palladium-catalyzed oxidative annulation of non- or weakly activated 1,3-dienes with 2-aryl cyclic 1,3-dicarbonyl compounds is described. Examples of the dearomatizing oxidative annulation of 1,3-dienes with 1-aryl-2-naphthols are also presented.